Parallel analysis of tri-molecular biosynthesis with cell identity and function in single cells - Samuel C. Kimmey (Nature Portfolio, 2019)
Simultaneous quantification of DNA, RNA and protein at the single cell level has not yet been possible. Here the authors introduce a molecular labelling and detection strategy to quantify synthesis of these biomolecules and couple it to transient cell states through parallel quantification of state-dependent biomolecules.